2014
DOI: 10.1111/ped.12191
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic markers of serious bacterial infections in febrile infants younger than 90 days old

Abstract: Background: The aim of this study was to assess correlations between demographic, clinical and laboratory characteristics and the risk of serious bacterial infection (SBI) in febrile <90-day-old infants. Methods: Medical records of all infants younger than 90 days old hospitalized at Dana-Dwek Children 's Hospital (2006's Hospital ( -2008 for evaluation of fever were retrospectively reviewed. Data on clinical, laboratory and demographic characteristics were retrieved and evaluated.Results: Forty-eight of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
1
6

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 27 publications
1
19
1
6
Order By: Relevance
“…Previous studies on <90 days old babies reported the rate of bacterial meningitis and aseptic meningitisas 0.2% and 14.4%, respectively [25]. In the studies, where only neonates were included, the rate of bacterial meningitis was 0.5-4.4% [2,[11][12][13].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies on <90 days old babies reported the rate of bacterial meningitis and aseptic meningitisas 0.2% and 14.4%, respectively [25]. In the studies, where only neonates were included, the rate of bacterial meningitis was 0.5-4.4% [2,[11][12][13].…”
Section: Discussionmentioning
confidence: 99%
“…The combination of procalcitonin with urinalysis was reported as more sensitive for identifying SBI in babies between 2 and 60 days old [28]. Recently, Nosrati reported that CRP was the only parameter found to be significantly associated with SBI (odds ratio, 1.042; 95% confidence interval CI: 1.028-1.056) in febrile infants [25].…”
Section: Discussionmentioning
confidence: 99%
“…[5][6][7] Se ha informado que la proporción de pacientes con aumento de los leucocitos (> 15 x 10/µL) era similar en los pacientes con neumonía bacteriana y viral. 12 Moulin y col. determinaron que la sensibilidad era del 65,1% y la especificidad era del 79,3% respecto del recuento de leucocitos (> 15 x 10/µL) para diferenciar entre la neumonía bacteriana y la viral.…”
Section: Discussionunclassified
“…Los marcadores de fase aguda más frecuentemente utilizados en la práctica clínica son el recuento de leucocitos, el recuento absoluto de neutrófilos, la velocidad de sedimentación globular (VSG), la concentración de proteína C-reactiva y de procalcitonina. [5][6][7] La prueba de reacción en cadena de la polimerasa (PCR) LightCycler ® SeptiFast MGRADE ayuda a detectar microorganismos patógenos en 6 horas, brindando un diagnóstico rápido y temprano de bacteriemia. 8 Se realizó este estudio para investigar el valor de las proteínas de la fase aguda y la prueba LightCycler ® SeptiFast para diferenciar las infecciones bacterianas de las virales.…”
Section: Introductionunclassified
“…13,14 Given that there is no consensus on the specific cut-off value for CRP that should be used to distinguish high and low risk of SBI in infants with fever, each author chooses the value to be used. Typically, in studies it varies in the range from 20 to 70 mg/L 19 , provided that for the population up to 90 days old most frequently used value is 20 mg/L 8,11,12,20 . Our cut-off value of 13.3 mg/L is somewhat lower than theirs, but close to the one used in a research by Zarkesh et al 10 , whose diagnostic value of CRP (sensitivity 81.6% and specificity 89.8%) shows results comparable to ours.…”
Section: Discussionmentioning
confidence: 99%